As práticas letradas e não letradas no Programa Brasil Alfabetizado em Campina Grande-PB - Guedes, Rosinete Barbosa (2011)
We take into account that the teaching practice adopted in the Programa Brasil Alfabetizado in Campina Grande (including the didactic material) correspond neither to the objectives nor to the proposals of the referred program, nor to its assessment. In order to carry out the study, we analyzed the teachers‟ education, the available material, the teaching practice and the PBA evaluation devices. Thus, this thesis aims at understanding how the teaching practice related to the teaching of the mother tongue within the PBA CG, through on-going education, contributes for effective adequacy to the objectives and evaluation of the program at national level. The theoretical framework is based on Freire (1983), Perrenoud (1999), Soares (2002), Kleiman (2004), Marcuschi (2004). We consider that literacy practices in emergency programs are only possible if there are effective public policies for teacher education considering that the teacher is the main literacy agent. The results achieved through the research lead us to the following conclusion: although the proposal of the program views literacy practices as an alternative for writing and reading acquisition, such result can be achieved only if there is an investment on on-going teacher education. In the present work, the result is positive due to the researcher‟s intervention, enabling the teacher to reflect on her practice of teaching Portuguese as a mother tongue and rendering possible a change in relation to the planning and the development of her own practice, which constitute part of the on-going education.